Biology learning model to improve critical thinking skills of ten grade students: A meta-analysis - Ma'lumatul Fuadiyah; Bunga Ihda Norra; Fuji Astutik (Assimilation: Indonesian Journal of Biology Education, 2022)
Critical thinking skill is one of the higher-order thinking skills which has to be mastered by students. However, many studies showed that students' critical thinking skills are still relatively low. So, it is necessary to carry out learning activities that can increase critical thinking skills, one of that is through the application of learning models. The purpose of this study was to find out the types of biology learning model that can improve the critical thinking skills of class X students, the biology learning model that was most recommended to improve the biological critical thinking skills of class X students in terms of effect size value, and biology learning model that was most recommended to improve students' critical thinking skills in each material content of class X in terms of the effect size value. The type of research used was quantitative research with the research method used in the form of meta-analysis. The results of the study revealed that there were 17 types of learning models that were proven to be able to improve the biological critical thinking skills of class X students. The guided discovery learning model based on e-learning was proven to have the highest effect size value of 1,07. The learning model which was recommended to improve the critical thinking skills based on material includes: problem-based learning for biodiversity material, think pair share (TPS) cooperative model for environmental pollution material, problem-based learning combined with student facilitator and explaining for fungi, and guided discovery and e-learning based learning for ecosystem materials.